Short report: Encephaloceles in Nigerian Igbos. Issue 7 (July 1977) - Onuigbo, Wilson I. B.
Abstract : A survey of surgical specimens submitted to a central laboratory suggests that the Igbos of Nigeria are a further ethnic group in whom the anterior encephalocele is comparatively common.